1995
DOI: 10.1016/s0022-5347(01)66705-3
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aspects of Prostate Cancer: A Case Control Study

Abstract: Men with a family history of prostate cancer are at a significantly increased risk for prostate cancer, especially if the affected relative had early onset of cancer. Prostate cancer does not seem to be associated with a higher incidence of other cancers in family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 10 publications
1
52
0
2
Order By: Relevance
“…African American mortality rates (6.7 per 100,000) have been about 3 times that among whites (2.6 per 100,000), which is also primarily attributed to the excess incidence of cervix cancer among African American women age 65 and over (3). Between 1973 and 1991, the incidence of invasive cervical cancer decreased for both African Americans and whites by 55 Although the incidence and mortality rates associated with prostate cancer are higher among African Americans than whites in the United States, there are wide variations in the incidence of prostate cancer among African populations (47). In Nigeria and the Caribbean, prostate cancer incidence is much lower than among African Americans.…”
Section: Uterine Cervixmentioning
confidence: 99%
See 1 more Smart Citation
“…African American mortality rates (6.7 per 100,000) have been about 3 times that among whites (2.6 per 100,000), which is also primarily attributed to the excess incidence of cervix cancer among African American women age 65 and over (3). Between 1973 and 1991, the incidence of invasive cervical cancer decreased for both African Americans and whites by 55 Although the incidence and mortality rates associated with prostate cancer are higher among African Americans than whites in the United States, there are wide variations in the incidence of prostate cancer among African populations (47). In Nigeria and the Caribbean, prostate cancer incidence is much lower than among African Americans.…”
Section: Uterine Cervixmentioning
confidence: 99%
“…A hospital-based study found a 2-fold elevated risk among men who had a father or brother with carcinoma of the prostate (55 diagnosed with this type of cancer than among whites (Tables 3,4). The higher incidence among whites is primarily due to excess localized tumors, whereas the incidence of more advanced tumors is similar among both racial groups (60).…”
Section: Uterine Cervixmentioning
confidence: 99%
“…Epidemiological studies have shown that the risk of prostate cancer is increased two-to threefold for male first-degree relatives of men with prostate cancer. Many of them have indicated that the risk may be higher for brothers than for sons of men with prostate cancer (Hayes et al, 1995;Keetch et al, 1995;Monroe et al, 1995;Narod et al, 1995;Whittemore et al, 1995;Lesko et al, 1996;Schaid et al, 1998;Bratt et al, 1999). These findings led to the hypothesis that prostate cancer susceptibility may be transmitted by X-linked or recessive inheritance in some families (Monroe et al, 1995), and recently a prostate cancer susceptibility gene was located to the long arm of the X chromosome (Xu et al, 1998).…”
mentioning
confidence: 99%
“…1,11 However, the two well-known risk factors for developing prostate cancer are increased aging and the presence of gonadal androgenic hormones. 1 Other factors recently studied include hereditary and familial factors (genetic predisposition), [20][21][22] African-American descent, [23][24][25][26] high-fat diet, 1,27 smoking and alcohol intake, 1,28 sexual relationships and prior vasectomy, 1 and vitamin D deficiency. It has been shown that the use of a combination of DRE, PSA and TRUS yields the best prostate cancer detection rate.…”
Section: Discussionmentioning
confidence: 99%